Fortification of diets with omega-3 long-chain polyunsaturated fatty acids enhances feedlot performance, intramuscular fat content, fat melting point, and carcass characteristics of Tattykeel Australian White MARGRA lambs - Pewan, Shedrach Benjamin; Otto, John Roger; Kinobe, Robert Tumwesigye; Adegboye, Oyelola Abdulwasiu; Malau-Aduli, Aduli Enoch Othniel (Frontiers in Veterinary Science, 2022)
Meat eating quality indices of intramuscular fat content (IMF) and fat melting point (FMP) of the Longissimus thoracis et lumborum muscle, feedlot performance, carcass traits and commercial wholesale cuts of lot-fed Tattykeel Australian White (TAW) MARGRA lambs in response to fortification of diet with omega-3 long-chain polyunsaturated fatty acids (n-3 LC-PUFA) were evaluated. The study utilized seventy-five TAW MARGRA lambs at six months of age with an average liveweight of 30 ±1.2kg. The lambs were randomly allocated to the following three dietary treatments of 25 lambs each, in a 47-day feeding trial using a completely randomised experimental design: (1) Control diet of hay plus pellets without omega-3 oil, (2) hay plus commercial whole grain pellets (MSM) without omega-3 oil, and (3) hay plus pellets fortified with omega-3 oil. It was hypothesized that dietary supplementation with omega-3 fortified pellets will improve feedlot performance, meat eating quality indices of IMF, FMP and carcass characteristics. Lot-fed lambs on the MSM whole grain had the highest feed intake of 1.69 kg/day, followed by the Control at 1.57 kg/day and lowest in the omega-3 diet at 1.01 kg/day (p = 0.0001). However, the omega-3 diet that had the highest average daily gain of 230g/head/day (p = 0.0001), indicating the greatest feed efficiency since it had the best growth response with minimal feed intake. Post-slaughter evaluation of the Longissimus thoracis et lumborum muscle revealed significant treatment variations in IMF (p = 0.0001), FMP (p = 0.0001), pH (p = 0.0380) and wholesale French rack primal cut (p = 0.0001). Strong correlations (p < 0.05) between liveweight, temperature, pH, FMP and IMF were observed. Similarly, significant correlations between carcass characteristics of total saleable meat yield, lean trim, fat trims, bones, and leg shank were evident (p < 0.05). The findings indicate that feedlot performance, meat eating quality traits of IMF and FMP as well as commercial wholesale French rack cuts can be further enhanced during feedlot finishing of TAW MARGRA lambs through dietary supplementation with omega-3 oils, hence an acceptance of the tested hypothesis of improved meat quality attributes.